Aghrāḍu “Yā” al Nidā’i fī Sūrati al A’rāfi wa Hūd (Dirāsatun Taḥlīliyyatun Balāghiyyatun fī ‘ilmi al Ma’āniy) - Mangsur, Jadub; Ardabli, Aziz (Jurusan Bahasa dan Sastra Arab Fakultas Adab dan Humaniora UIN Sulthan Thaha Saifuddin Jambi, 2020)
Al-qu'an is the first source of Islamic law، which is obligatory for all muslims to do. To understand the Qur'an، it is necessary to master the sciences of Arabic، especially balaghah، among them the objectives of Nida'. In the Qur'an there is a lot of Nida' in which there is the meaning of qiyasi،which has been mentioned in the balaghah books. To know the purpose of the verse contained the letter Nida' ، the author did a study with the title